Preliminary Results From a Randomized Controlled Study for an App-Based Cognitive Behavioral Therapy Program for Depression and Anxiety in Cancer Patients - Ham, Kyunghee; Chin, Siyung; Suh, Yung Jae; Rhee, Myungah; Yu, Eun-Seung; Lee, Hyun Jeong; Kim, Jong-Heun; Kim, Sang Wun; Koh, Su-Jin; Chung, Kyong-Mee (Frontiers in Psychology, 2019)
From the time of their diagnosis, cancer patients experience various psychological and social difficulties, the most common being depression and anxiety. The purpose of this study was to develop and evaluate the effectiveness of an app-based cognitive behavioral therapy program (HARUToday) for depression and anxiety in cancer patients using both questionnaires and computer tasks. For this purpose, 47 participants who met the inclusion criteria were randomly assigned to either the cognitive behavioral therapy program, a simple information-provision program (HARUCard), or a waitlist control group. Self-report questionnaires and two computer tasks were administered before and after 66 days of intervention. The results showed that the depression and anxiety scores of the HARUToday group decreased significantly after intervention compared to the other two groups. However, there was no significant change in scores on the Health-Related Quality of Life scale, Dysfunctional Attitude Scale, and the two computer tasks (Dot probe task and Implicit Association Test). Such results suggest that HARUToday may be an effective intervention for alleviating depression and anxiety in cancer patients. The limitations of this study and suggestions for future research are discussed.